Teaching Anxiety, Efficacy, and Immersive Experience in VR-Based Microteaching among Elementary Pre-Service Teachers in Rural Context - Eli Meivawati; Zuhra Meiliza; Husnul Khatimah; Asmirinda Resa; Hilman Qudratuddarsi; Hazlynda Bt Atta (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2026)
Abstract: Teacher education in rural contexts faces challenges related to limited teaching practice opportunities, technological access, and pedagogical support, which may affect pre-service teachers’ instructional readiness. This study examines the roles of teaching anxiety, teaching efficacy, immersive learning experience, and interest in virtual reality in shaping basic teaching skills through virtual reality–based microteaching among elementary pre-service teachers in rural contexts. A quantitative explanatory design was employed involving 205 pre-service teachers from the Primary School Teacher Education program at Universitas Sulawesi Barat. Data were collected using a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling. The findings indicate that immersive learning experience has a strong positive effect on basic teaching skills (β=0.501, p<0.001), followed by teaching efficacy (β=0.372, p<0.001). In contrast, teaching anxiety shows a negative but non-significant effect (β = −0.043, p > 0.05). Additionally, interest in virtual reality positively influences immersive learning experience (β=0.330, p<0.001) and indirectly contributes to basic teaching skills through immersion (β =0.165, p<0.01). The model explains 61.3% of the variance in basic teaching skills (R²=0.613). These results highlight the potential of virtual reality–based microteaching as an effective approach for developing pedagogical skills among elementary pre-service teachers in rural educational settings. Abstrak: Pendidikan guru di daerah rural menghadapi berbagai tantangan, seperti keterbatasan kesempatan praktik mengajar, akses teknologi, dan dukungan pedagogis, yang dapat memengaruhi kesiapan mengajar calon guru. Penelitian ini bertujuan untuk mengkaji peran kecemasan mengajar, efikasi mengajar, pengalaman belajar imersif, dan minat terhadap virtual reality dalam membentuk keterampilan dasar mengajar melalui microteaching berbasis virtual reality pada calon guru sekolah dasar di daerah rural Sulawesi Barat. Penelitian ini menggunakan desain kuantitatif eksplanatori dengan melibatkan 205 mahasiswa PGSD Universitas Sulawesi Barat. Data dikumpulkan menggunakan angket terstruktur dan dianalisis dengan Partial Least Squares Structural Equation Modeling. Hasil penelitian menunjukkan bahwa pengalaman belajar imersif berpengaruh positif kuat terhadap keterampilan dasar mengajar (β=0,501; p<0,001), diikuti oleh efikasi mengajar (β=0,372; p<0,001). Sebaliknya, kecemasan mengajar menunjukkan pengaruh negatif namun tidak signifikan (β =−0,043; p>0,05). Selain itu, minat terhadap virtual reality berpengaruh positif terhadap pengalaman belajar imersif (β=0,330; p<0,001) dan berpengaruh tidak langsung terhadap keterampilan dasar mengajar melalui pengalaman belajar imersif (β=0,165; p<0,01). Model penelitian mampu menjelaskan 61,3% variasi keterampilan dasar mengajar (R²=0,613). Temuan ini menegaskan bahwa microteaching berbasis virtual reality berpotensi menjadi pendekatan efektif dalam meningkatkan keterampilan pedagogis calon guru sekolah dasar di konteks pendidikan rural.